Lean adolescents achieve higher intensities but not higher energy expenditure while playing active video games compared with obese ones. Issue 2 (8th April 2015) - Chaput, J.P.; Genin, P.M.; Le Moel, B.; Pereira, B.; Boirie, Y.; Duclos, M.; Thivel, D.
Summary: Background: While decreased physical activity and increased sedentary behaviours are incriminated for their role in the progression of obesity, active video games (AVG) may offer a new alternative to increase energy expenditure in youth. This study is the first to examine the effect of a 1‐h AVG play on lean and obese adolescents' energy expenditure. Methods: Body composition and aerobic fitness were assessed in 19 obese and 12 lean adolescent boys (12–15 years old). Participants performed a 1‐h AVG session (Kinect Sports technology) while wearing a portable indirect calorimeter (K4b2) to assess their energy expenditure and heart rate. Results: Body weight (91.0 ± 9.5 vs. 58.5 ± 12.4 kg), body mass index (32.2 ± 3.1 vs. 20.3 ± 1.6 kg m −2 ) and body fat (38.1 ± 2.7 vs. 13.4 ± 3.9%) were significantly higher in obese adolescents ( P  < 0.001). Absolute energy expenditure was significantly higher in obese ( P  < 0.05) but not when corrected for body composition. Maximal heart rate reached during AVG was significantly higher in lean adolescents (190 ± 25 vs. 183 ± 28 bpm, P  < 0.05). Time spent between 3 and 6 METs (Metabolic Equivalent Task) was not different between groups but time spent above 6 METs was higher in lean adolescents ( P  < 0.05). Conclusion: Although lean and obese adolescent boys experienced similar energy expenditure relative to their body size during a 1‐h Kinect AVG session, lean adolescents spent more time in moderate‐to‐vigorous physical activity.